Portuguese Ministers, 1851-1999: Social Background and Paths to Power - Almeida, Pedro Tavares de (2014)
Disponível em: http://193.136.113.6/Opac/Pages/Search/Results.aspx?SearchText=UID=bb8aa8d5-c6b6-466a-81bb-fe8a67693cee&DataBase=10449_UNLFCSH